2019
DOI: 10.1021/acs.jpcb.9b07021
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Hydration Dynamics and Cooperative Interactions in Glycerol–Water Mixtures by Terahertz Dielectric Spectroscopy

Abstract: We report relaxation dynamics of glycerol-water mixtures as probed by megahertz-to-terahertz dielectric spectroscopy in a frequency range from 50 MHz to 0.5 THz at room temperature. The dielectric relaxation spectra reveal several polarization processes at the molecular level with different time constants and dielectric strengths, providing an understanding of the hydrogen-bonding network in glycerol-water mixtures. We have determined the structure of hydration shells around glycerol molecules and the dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 51 publications
(139 reference statements)
6
32
0
Order By: Relevance
“…These features could be due to changes in hydrogen bonding network as we change the glycerol-water composition. A parallel trend was observed in the dielectric and THz study performed by Vinh and coworkers, 21 in aqueous solutions of glycerol. In that work, four hydrogen bonding networks were proposed, bulk water, solvated water, confined water and bulk glycerol.…”
supporting
confidence: 70%
“…These features could be due to changes in hydrogen bonding network as we change the glycerol-water composition. A parallel trend was observed in the dielectric and THz study performed by Vinh and coworkers, 21 in aqueous solutions of glycerol. In that work, four hydrogen bonding networks were proposed, bulk water, solvated water, confined water and bulk glycerol.…”
supporting
confidence: 70%
“…The average number of intermolecular hydrogen bonds increases with the increase in molecular size of the osmolyte in the following order: ethanol < urea < glycerol < sorbitol ∼ α-glucose ∼ β-glucose < trehalose (Table ). The values of 15.8 for trehalose and 5.9 for glycerol are comparable to the experimentally determined hydration number of 16–18 for trehalose and 5.58 for glycerol . We find a urea molecule on average to form 5.3–5.5 hydrogen bonds, in close agreement with the value of 5.7 estimated from the empirical potential structure refinement (EPSR) simulation characterizing neutron scattering data of urea solutions.…”
Section: Resultssupporting
confidence: 84%
“…The values of 15.8 for trehalose and 5.9 for glycerol are comparable to the experimentally determined hydration number of 16−18 for trehalose 74 and 5.58 for glycerol. 75 We find a urea molecule on average to form 5.3−5.5 hydrogen bonds, in close agreement with the value of 5.7 estimated from the empirical potential structure refinement (EPSR) simulation characterizing neutron scattering data 38 of urea solutions.…”
Section: ■ Introductionsupporting
confidence: 85%
“…[9,11,12] While experimental evidence does reveal features such as longer residence times and restricted rotational dynamics of water molecules at the interface with ionic solutes, there is little evidence to support the claim that such water molecules are immobilized to the extent that they cannot participate in ice formation even at low temperatures. [14][15][16][17][18][19] Furthermore, while some have observed that the appearance of bulk-like water within a polymer substantially impacts its physical properties, the specific relationship between the amount of melting water and the bulk properties of the hydrated polymer remains poorly understood. [20,21] Fourier transform infrared spectroscopy (FTIR) is another experimental method that has been used to probe the behavior of water in hydrated polymers.…”
Section: Introductionmentioning
confidence: 99%